The implementation of solar photovoltaic installation on the rooftop of UTHM buildings / Ahmad Azfar Roslan and Zainal Abidin Akasah - Roslan, Ahmad Azfar; Akasah, Zainal Abidin (2018)
Renewable energy has become one of the largest sources to produce electricity consumption in our daily use, most notably energy from the sun. Malaysia receives enough energy from the sun to generate a noteworthy amount of electricity. Malaysia can tap this incredible potential energy initiative. The Malaysian government wants total electricity to come from renewable energy sources. However, Malaysians still do not prefer to use the renewable energy sources for energy consumption in daily life. Ironically, even UTHM does not play a role as a public university in implementing the government's intention to uplift the renewable energy industry. This study was conducted to investigate the total area (number?) of selected buildings that could possibly install the Solar PV panel towards the diffusion of the sun's irradiation. For this study, there are three phases conducted. The first phase is gaining data on electricity consumption; the second phase is fieldwork; and lastly is design phase. All these three phases were conducted in order to achieve the objectives of implementation and installation of Solar PV for UTHM buildings. The outcome of this study is the proposed design of energy consumption from Solar PV panels for UTHM buildings.